Penerapan Green Accounting terhadap Kinerja Lingkungan (Studi Kasus pada Perusahaan Sektor Pertambangan dan Energi yang Listing di Bursa Efek Indonesia Tahun 2014-2020) - Efi Risqi Amaliyah; Dewita Puspawati (Prosiding University Research Colloquium, 2022)
This research purpose to test the effect of the application of green accounting on environmental performance. The sample in this study is a mining and energy sector company that was listed on the Indonesia Stock Exchange in 2014-2020 using a sampling technique that is purposive sampling. There are 5 companies that meet the criteria set as a sample in this study. The method of analysis in this study is multiple linear regression. The results showed that recycle materials, renewable energy and corporate social responsibility fund allocation had no effect on environmental performance. While the environmental cost effects environmental performance.